Measuring the Quality of Internal Control and its Impact on the Performance of the Banking Institutions - Haider Ali Abdullah (Technium Social Sciences Journal, 2024)
The researcher aimed to assess the impact on the institutional performance of the bank’s sample research, the statement of relationship, and the quality of internal control through his research. There were seven banks in the government commercial bank research community, and two banks were included in the sample research. To evaluate his research hypotheses, the investigator used a two-axis resolution distributed among 45 questions, totaling 68. A basic linear regression model was employed by the researcher. According to Pearson’s coefficient of correlation with the research findings, the study sample banks demonstrated both high levels of institutional performance and internal control quality. Additionally, it demonstrated a statistically significant relationship between the quality of internal control and the banking institution’s performance. Based on these findings, the researcher recommended that banks take a greater interest in internal control, which will help to improve the institutions’ overall performance.